INCREASING PATIENT SATISFACTION: THE EFFECT OF SERVICE QUALITY, STANDARD OPERATING PROCEDURES (SOP), AND COMPETENCE, CASE STUDY AT A HOSPITAL IN JAKARTA - Rulandari, Novianita (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Based on patient satisfaction data at Mulyasari Hospital Jakarta January to. In May 2021, patient satisfaction was found to be 80.34% below 95%, thus requiring improvements in service. Many patients complain about the lack of facilities, such as parking space, incomplete medical equipment, sloppy administration, lack of medical personnel, discipline of medical personnel, slow hospital response in handling complaints, and standard operating procedures (SOP) that are still not optimal. The aim of this research is to analyze whether there is an influence between service quality, standard operating procedures, competency of medical personnel, and patient satisfaction. In this research, the sample was used using the Structural Equation Model (SEM). The number of indicators in this study was 61 indicators, and the sample in this study was 305 people, using an accidental sampling technique. The research results concluded that there was an influence between Service Quality (X1), Standard Operating Procedures (SOP) (X2), Competency of Medical Personnel (X3) on Patient Satisfaction (Y).